RELATIONSHIP AMONG ARTERIAL STIFFNESS PARAMETERS AND TARGET ORGAN DAMAGE. (April 2021) - García, Fernando Martínez; De Gracia, Ana; Calaforra, Oscar; Solaz, Elena; Vicente, Antonio; Pichler, Gernot; Redon, Josep
Abstract : Objective: Carotid-femoral (cf) PWV is considered the gold standard for arterial stiffness (AS) but other different parameters can add information about systemic or local AS. Whether that information is clinically redundant or complementary is currently unknown. We analyzed the relationship among different AS parameters to each other and with a target organ damage (TOD) score. Design and method: AS data were retrospectively evaluated in a sample of 1031 hypertensive patients. Cf-PWV and Augmentation index (Aix) by peripheral applanation tonometry (PAT) were determined with an SphygmoCor® device. Local PWV, local Aix, Ep module, Beta parameter and arterial compliance were determined by echo-tracking at the carotid level with an Aloka ultrasound (US) device. Left ventricular mass (LVM) was assessed by echocardiography, intima-media thickness (IMT) and plaques by carotid US and albumin-creatinine ratio (ACR) by immunonephelometry. A 24 points subclinical target organ damage (TOD) score was created using not only qualitative (presence or absence) but also quantitative information (magnitude of damage). The relationship among parameters of AS to each other and with the score of TOD were established by Pearson or Spearman correlation coefficients. Results: There was a significant relationship between cfPWV and the score of subclinical TOD, the higher the score, the higher the PWV (r = 0.19, p-value < 0.05). Figure. No caption available. All echo-tracking parameters, particularly the Ep module were also significantly related to the score but not the Aix by PAT. There were significant correlations among the different measures of AS to each other. The highest correlation was found between the Aix determined by tonometry and local Aix determined by carotid echo-tracking (r = 0.71, p-value < 0.05). By contrast the correlation between the cfPWV and local carotid PWV was very low (r = 0.28, p-value < 0.05). Conclusions: There was a significant correlation among different AS parameters and probably these parameters may add extra information to the gold standard (cfPWV). The presence of an increase in AS parameters is linearly related with the presence of subclinical TOD at other levels. Further studies are needed to determine the clinical prognostic values of combined AS parameters.